ECONOMIC GEOGRAPHIES: Navigating Research and Activism - Dombroski K; Roelvink G (Massey University, 2022)
This chapter focuses on a sub-field of economic geography that has activism at its core: community economies. We begin by situating community economies research within economic geography, in doing so placing our methodological discussion in the context of broader intellectual trends. The chapter then focuses on three challenges shaping community economies methodology today. In contextual challenges of uncertainty, we explore how community economies researchers are “staying with the trouble” (Haraway, 2016), rejecting simplification in favour of unknown yet hopeful possibility. Embracing our work as a ‘performative ontological practice', community economies research has a clear political agenda in this methodological ‘making of other worlds', one that is guided by ethical economic principles and practice. A central challenge in this work is how our methodology, and use of particular methods, is created and enacted with human and more-than-human others. This includes working with those of other intellectual traditions and different ontologies and well as more-than-human participants whose agency is often not recognized.